Capacidade para o trabalho entre trabalhadores - Cordeiro, Técia Maria Santos Carneiro e (2014)
Considering the context about the health of the worker and the work ability, this dissertation has as objectives: to describe the prevalence and factors associated with work ability among workers from Brazil; evaluate factors associated with work ability among nursing workers of the primary health care in Bahia, Brazil; and to evaluate validity of indicators of the work ability index among health workers in Bahia, Brazil. For that, constitutes three scientific articles: 1 – Work ability among workers in Brazil: a systematic research; 2 – Work ability among nursing workers of the primary health care; 3 –Validation of the Work Ability Index - WAI among health workers. It is considered that the work ability is a broad construct, complex and multidimensional that involves individual aspects, physical and mental, organizational and of the work environment. The inadequate work ability of the nursing workers was associated with the bond of effective work, the work done in just one turn, have developed occupational disease, being dissatisfied with the work ability and live in high strain job. The work ability index showed itself as an instrument capable of measuring the work ability of health workers in primary health care and medium complexity through three dimensional factors related to mental resources, work ability physical and mental, and work ability in the presence of diseases and restrictions on health status. It is expected that this study will stimulate further research in the context of occupational health and that the work ability index can be used in studies with similar populations. So long, becomes necessary intervention in the organizational aspects of work environments to promote, maintain and restore the work ability, as well as the implementation of health work programs for quality and accessible to promote active aging.